High-Aspect-Ratio Dye-Sensitized Solar Cells Based on Robust, Fast-Growing TiO2 Nanotubes - So, Seulgi; Lee, Kiyoung; Schmuki, Patrik (Chemistry - A European Journal, 2013)
The mechanical attachment of TiO2 nanotube layers to a substrate can be a determining factor for the performance of these layers in dye-sensitized solar cells (DSSCs). Self-organized TiO2 nanotube layers grown in an electrolyte that contained lactic acid are shown to have considerably improved anchoring on the Ti metal substrate, which allows the construction of stable and efficient solar cells with >50 extgreekmm nanotube length.
EAM Import::2019-03-13